Macroscopic and Mesoscopic Mechanical Properties of Mine Tailings with Different Dry Densities under Different Confining Pressures. (30th September 2020) - Zhang, Zhi-jun; Guo, Yao-hui; Tian, Ya-kun; Hu, Lin; Wang, Xi-xian; Zheng, Huai-miao; Wu, Ling-ling
Abstract : Particle flow numerical simulation software (PFC 3D ) was utilized to establish the consolidated-undrained triaxial compression test numerical models of mine tailings with different dry densities to deeply investigate the macroscopic and microscopic characteristics of mine tailings in a tailing pond in Hunan Province. Comparing the results of the simulation and the laboratory experiment, the mesoscopic parameters of the particle flow numerical simulation were obtained through continuously adjusting the mesoscopic parameter with the higher degree of agreement between the stress-strain curve, the peak strength, and the elastic modulus as the determining standard. The macroscopic and microscopic characteristics of mine tailings were studied from the perspectives of stress-strain, axial strain-volume strain, coordination number, particle velocity vector, and contact force between particles. After numerous numerical tests, it was found that the PFC 3D simulation results are consistent with experiment results of the dry density tailing samples under different confining pressures; compared with the high confining pressure, the simulation test results at lower confining pressures were more with that of the laboratory tests; low density and high confining pressure both have inhibitory effect on the dilatancy characteristics of triaxial samples; with the same confining pressure, the dilatancy tendency of low dry density samples is suppressed comparing with the high dry density samples. The initial coordination number of the numerical model is large, which proves that the contact degree of the model is good to some extent.